Մովսես Խորենացու երկի մի քանի գրական առանձնահատկությունների մասին - Եղիազարյան, Ազատ («Նաիրի» հրատ.)
The “History of the Armenians” by Movses Khorenatsi is one of the most important monuments of Armenian historiography. Yet its literary peculiarities are not studied sufficiently. I am based on the conviction that it is not a fiction, but not a scientific work either. It has its specific features, which I try to find out in my paper. The most essential characteristic is the style of his narrative, which I have focused on.
Keywords: Բանասիրություն